Kontestasi Jasa Jual Sarana Ritual Umat Hindu Dan Islam Sebagai Implementasi Moderasi Beragama - Budhawati, Ni Putu Sudewi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This research aims to find out about the implications and strategies of contestation of selling services for Hindu and Muslim ritual facilities as an implementation of religious moderation in the Karang Lelede Mataram market. This research is a qualitative study with a sociological approach, determining informants in this study using purposive techniques and data collection techniques used are observation, interviews and documentation studies. Data analysis in this study was carried out during and after data collection using qualitative data analysis flow model developed by Miles and Huberman with the stages of reduction, data presentation and verification. Data analysis is presented in the form of reduction, classification, display and interpretation. The results showed that: 1) The contestation of selling services of Hindu and Islamic ritual facilities occurs due to the lack of understanding of the traders on the importance of religious moderation, 2) The implications of the contestation of selling services of Hindu and Islamic ritual facilities have unfavourable implications for social relations between traders due to sales competition and price instability of ritual facilities sold between traders from Hindus and traders from Muslims, 3) The strategy of maintaining religious moderation in the contestation of selling services of Hindu and Islamic ritual facilities in Karang Lelede Mataram market is done by strengthening Religious Harmony, fostering national commitment and developing tolerance.